STRATEGI PENGELOLAAN PARIWISATA DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH(PAD) STUDI KASUS PADAOBYEK WISATA PAKET SEMARAPURA CITY TOUR DI KABUPATEN KLUNGKUNG - Triana Wulandari, Ni Komang Novi; Winaya, I Ketut; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2019)
ABSTRACT The tourism sector has the potential to be developed as a source of regional. To increased (PAD), the government need to develop and facilitate tourism sited so that the tourism sector could contribute for economic development. The purpose of this study was to find out what strategy managing tourism in increasing locally-generated revenue (PAD). The result of this study indicated adopted by the Klungkung District tourism management to increased local revenue.This research produced alternative strategized for SO (Strenghs-Opportunities) namely, established special management bodies in every tourism object, utilized technology as a marketing medium in an effort to increase the number tourism visited that have an impact on increasing Semarapura City Tour tourism revenue. Keywords: Strategy, Locally-generated Revenue (PAD), Semarapura City Tour